THE SILK ROAD ECONOMIC BELT POLICY IN SUPPORTING CHINESE GEOPOLITIC PROJECTIONS IN THE REGION - Sony Iriawan (Indonesia Defense University, 2020)
The Chinese government's policy in The Silk Road Economic Belt aims to facilitate the infrastructure of land route transportation. Railway infrastructure projects and installation of oil and gas pipelines require a large investment, and Chinese political power to influence every country to support and be involved in the Belt Road Initiative project. The direction of the Chinese government's policy is certainly intended to underpin China's geopolitical projections in the region. The research question is analyzed through theory of geopolitics, geostrategy and geoeconomics. The research methodology, based on descriptive analytic, is supported by data collection techniques and is equipped with data sources relevant to the phenomena discussed. In conclusion, China's geopolitical projections become the main goal for the Chinese government in the Silk Road Economic Belt policy. The assumption of the geopilitical theory of the heartland illustrates that the mastery of the land logistics route supports China's efforts to influence globally by building a logistics path that further connects China with the global world, including Europe, Asia, the Middle East and North Africa.Keywords: China, Geopolitics, The Silk Road Economic Belt.